Determinants of dividend yield of Malaysian firms - Liew, Teresa Phit Sia (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study focuses on the perfonnance of 788 finns over a 10-year period from year 2000 to 2009 that provide infonnation on market capitalization, net income, tota~ assets, total common equity, net operating cash flow, the earning per share and the date the finn was first listed on Bursa Malaysi, The result of statistics summary provide support to the previous studies that Malayslan dividend payers are more profitable, having higher net operating cash flow and investment opportunities but lower debt equity ratio than the non-payers. The result of Logit regression shows that profitability has the strongest positive influence, debt equity has moderate negative influence and cash flow has mild positive influence on the probability of dividend yields. Investment opportunities have been found with no significant contribution. The influence of the financial variables on dividend yield varies when finns are examined within the context of size and age of finns. The only exception here is profitability which consistently shows positive influence and its impact increases across size and age of finns.